Modeling and Design of a Solar Rotary Dryer Bench Test for Phosphate Sludge - Khadija Ettahi; Meriem Chaanaoui; Vaudreuil Sébastien; Souad Abderafi; Tijani Bounahmidi (Modelling and Simulation in Engineering)
As an eco-friendlier way to manage mining waste, the use of solar energy to dry phosphate sludge in a rotary dryer is envisioned. As a first step toward this end, a design study for a bench-scale rotary dryer for phosphate sludge is detailed, using a one-dimensional mathematical model developed for this task. Using the Engineering Equation Solver (EES) software, a steady-state transport phenomena model was developed that enables an estimation of the moisture and temperature profiles for both gas and product in the dryer. A sensitivity analysis evaluated the effects and influence of different geometric parameters and operating conditions on the product moisture profile. Parameters involved include the diameter of the dryer, the residence time of the product to dry, inlet air temperature, and inlet product humidity. This allowed for the selection of suitable design parameters for the operation of a phosphate sludge dryer with a 1.5 m length and an internal diameter of 11.5 cm. The inlet air temperature of the rotary dryer was set at 200°C to achieve a reduction of moisture content in the product from 30% to 7%. The model was validated through literature and experimental datasets, with an error averaging 0.22% and 1.52%, respectively.